Pengaruh Pemanfaatan Teknologi Digital Terhadap Kinerja UMKM di Era Transformasi Digital - Putri, Mirza Hidayah; Serlyta, Serlyta; Noviyanti, Indah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study aims to analyze the influence of digital technology utilization on the performance of micro, small, and medium enterprises in the era of digital transformation. The research employed a quantitative approach with a survey method, in which data were collected through closed-ended questionnaires distributed to one hundred micro, small, and medium enterprise actors from various business sectors in Indonesia. The independent variable in this study is the utilization of digital technology, measured through three main indicators: access to and ownership of digital technology, the use of social media and online platforms, and digital literacy. The dependent variable is business performance, which includes aspects of marketing, finance, human resources, and operations. Data analysis was conducted using simple linear regression with the assistance of statistical software. The results show that digital technology utilization has a significant influence on the performance improvement of micro, small, and medium enterprises. The use of social media and online platforms proved to be the dominant factor supporting performance enhancement across various business aspects. This study recommends strengthening digital literacy and ensuring sustainable policy support to accelerate digital transformation in the small business sector